Sport commitment among children and adolescent through the lens of theory of organismic integration: A systematic literature review - Anna Pavlova (Current Issues in Sport Science)
Introduction Most of the athletes who participate in the Olympic Games are between 20 and 30 years old. Popular sport therefore has a reserve of Olympic talent for the 2032-2044 cycles. The involvement of children and adolescents in sport contributes to their socialization, academic success and emotional stability, as well as to sustainable development goals in general. The purpose of this study is to identify potential areas for enhancing sport motivation in children and adolescents and to formulate the concept of sport identity based on organismic integration theory.